Coenagrion hastulatum (Charpentier, 1825), new for the dragonfly fauna of Bosnia and Herzegovina (Odonata: Coenagrionidae) - Matjaž Bedjanič (Natura Sloveniae)
At the high-altitude Donje Bare and Gornje Bare Lakes in the surroundings of Tjentište village, Zelengora Mts., Sutjeska National Park, SE Bosnia and Herzegovina, Coenagrion hastulatum was recorded on 26 June 2011. The occurrence of the species on the southern border of its European range is outlined and discussed. Faunistic records on a total of 22 spp. observed at 11 localities in the southeastern part of the country between 26 and 29 June 2011 are appended.